2013
DOI: 10.1002/jat.2897
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the allergenic potential of proteins: an assessment of the kiwifruit allergen actinidin

Abstract: Assessment of the potential allergenicity (IgE-inducing properties) of novel proteins is an important challenge in the overall safety assessment of foods. Resistance to digestion with pepsin is commonly measured to characterize allergenicity, although the association is not absolute. We have previously shown that specific IgE antibody production induced by systemic [intraperitoneal (i.p.)] exposure of BALB/c strain mice to a range of proteins correlates with allergenic potential for known allergens. The purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…We have not been able elucidate why Bublin et al observed aggregation of actinidin and the reasons for these different in vitro digestion results are poorly resolved. However, our results are in good correlation with in vivo and in vitro digestion experiments from other studies . Further experiments directly comparing the different methodologies employed are required to resolve the issue.…”
Section: Resultssupporting
confidence: 80%
“…We have not been able elucidate why Bublin et al observed aggregation of actinidin and the reasons for these different in vitro digestion results are poorly resolved. However, our results are in good correlation with in vivo and in vitro digestion experiments from other studies . Further experiments directly comparing the different methodologies employed are required to resolve the issue.…”
Section: Resultssupporting
confidence: 80%
“…Notably, the BALB/c mouse strain is considered to favor type 2 immune responses with atopic-like phenotype) [ 8 , 9 , 25 , 26 ]. Thus, this mouse strain has been widely used in the search for a validated murine model to evaluate the sensitizing or allergenic potential of proteins [ 4 , 5 , 8 , 9 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, most cases of food allergy are associated with a limited number of allergens, such as peanut, tree nuts, hen’s egg, cow’s milk, fish and shellfish, although the number of food allergens is large [ 2 , 3 ]. This could be attributed to an increased ability of these foods to sensitize and trigger allergic reactions and suggests that “a spectrum of allergenic or sensitizing potentials exists amongst food proteins” [ 4 ]. If such a spectrum does exist, the sensitizing potential of proteins, defined as the inherent capacity of proteins to trigger an IgE-mediated immune response, could be assessed not only in naturally occurring protein allergens, but also in food proteins derived from transgene products or proteins modified upon food processing.…”
Section: Introductionmentioning
confidence: 99%
“… 10 The importance of OVA stems not only from the high prevalence of egg allergy, the second more frequent food allergy in children below the age of 3, which affects up to 1.7% of children and adults, 11 but also because OVA is normally used as a model protein to investigate the molecular and cellular mechanisms of allergic sensitization and tolerance. 12 13 14 15 …”
Section: Introductionmentioning
confidence: 99%